Effects of internal migration on healthcare services utilization in Bangladesh: an analysis of nationally representative survey - Araf, Fardin; Haque, Md Rabiul; Angeles, Gustavo (Frontiers in Public Health, 2025)
BackgroundDespite the significance of internal migration as an important social determinant of health that could potentially affect the utilization of maternal healthcare services, the magnitude of this relationship by different migration streams is yet to be fully explored in Bangladesh.MethodsThis study using Bangladesh Demographic and Health Survey data, 2017–18 examined the effects of different migration streams on maternal healthcare service utilization, particularly four or more antenatal care (≥4 ANC) visits and institutional delivery (ID) care services.ResultsThe analysis identified significant variations in using antenatal and institutional delivery care services between migrants and non-migrants. The rural non-migrants were found to be the most disadvantaged group, particularly when different forms of migration streams were considered. For instance, after adjusting for covariates, urban to urban migrants (≥4 ANC = 1.866, p < 0.01; ID = 2.247, p < 0.001) and urban to rural migrants (≥ 4 ANC = 1.24, p > 0.05; ID = 1.689, p < 0.05) were more likely to utilize both types of maternal healthcare services than rural non-migrants. However, migrants of all streams were less likely to use any type of maternal healthcare services when compared against the urban non-migrants.ConclusionAddressing the effects of migration in designing and implementing maternal healthcare service delivery programs may address the needs and challenges faced by migrants.